Phase evolution of conversion-type electrode for lithium ion batteries - Jing Li (Nature Portfolio, 2019)
Conversion electrodes possess high energy density but suffer a rapid capacity loss over cycling compared to their intercalation equivalents. Here the authors reveal the microscopic origin of the fading behavior, showing that the formation and augmentation of passivation layers are responsible.